Extensive reading and its impact on Malaysian undergraduate ESL/EFL learners’ reading proficiency and reading motivation - Ker-hsin, Wan; Razali, Abu Bakar (Human Resource Management Academic Research Society, 2023)
English language reading skills are important for tertiary students. In Malaysia, tertiary students are required to master the English academic reading for their tertiary studies. However, Malaysian tertiary students’ reading proficiency in English is often found below par, which is attributed to poor reading skills and habits, as well as a lack of motivation to read. The authors believe that extensive reading (ER) should be used to complement intensive reading practiced in tertiary education reading. It is important to learn from past studies the potentials as well as problems with ER, so that teachers and researchers alike can better approach the use of ER in the teaching of English as a second language (ESL) reading. This article reports on the systematic literature review of 32 studies on ER programmes, particularly on its impact on ESL students’ reading proficiency and reading motivation, that were published between 2003 and 2019 and obtained through established research databases. The results of the review found that there are positive impacts of ER on ESL reading, particularly on reading rate and reading comprehension, vocabulary knowledge, and reading motivation, as well as the importance of goal setting and monitoring to ensure the success of ER in ESL reading. The authors suggest implications for teacher practitioners, future researchers and course developers to plan how ER would be a valuable addition to their respective programmes and also provide them with ideas in designing their own unique ER programmes to cater to their students’ needs.